RELATIONSHIP OF THYROID-STIMULATING HORMONE WITH METABOLIC SYNDROME IN A SAMPLE OF EUTHYROID PAKISTANI POPULATION - Saleem, Muhammad Shahzad; Shirwany, Tanvir Ali Khan; Khan, Khurshid Ahmad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Metabolic Syndrome is a group of factors that predispose to cardiovascular diseases. The prevalence of metabolic syndrome is rising rapidly. Recently, a few studies have suggested that lower thyroid function in the reference range may be associated with metabolic syndrome, but the issue remains unsettled. We aimed to elucidate the relationship between thyroid function and components of metabolic syndrome in a sample of euthyroid Pakistani population. Methods: This analytical, cross-sectional study was conducted at the Department of Physiology, University of Health Sciences, Lahore, Pakistan, and extended over a period of 12 months. It included 100 subjects with metabolic syndrome in the study group and thirty subjects without metabolic syndrome in the control group with age ranging 45-55 years. Both groups had normal thyroid function. After a detailed history and clinical examination, fasting blood was analysed for glucose, triglycerides, high density lipoprotein-cholesterol along with thyroid-stimulating hormone (TSH) and free thyroxine. Results: Serum TSH was significantly higher in study group than in control group (p=0.040). Serum free thyroxine values of study group were slightly but not significantly lower than those of control group. Serum TSH correlated significantly and positively with serum triglycerides in all subjects and with waist circumference and diastolic blood pressure in men. Serum TSH showed a positive and linear relationship with the number of components of metabolic syndrome (p=0.016) in all subjects. Conclusion: High-normal TSH is associated with metabolic syndrome and its components. There may be increased risk of cardiovascular diseases with high-normal TSH levels. Keywords: Thyroid Stimulating Hormone, Metabolic Syndrome, Euthyroid